The Impact of Security, Service Quality, Perceived Usefulness, Perceived Ease of Use, Trust, and Price Value on Users’ Satisfaction in Cloud-Based Payment Systems in Australia: A Pls-Sem Analysis - Mondego, Domingos; Gide, Ergun (Journal of Information Systems and Technology Management, 2024)
Over the past years, the ubiquity and versatility of cloud-based payment systems (CBPS) have become an evolutionary path in the payment process. However, despite is undeniable the various advantages of using the CPBS, compared to other countries the adoption rates are still very low in Australia. This suggests that people might not know the benefits of using them or they might not be satisfied with the current payment systems. In this context, the purpose of this research was to examine the impact of security and service quality on the factors (perceived usefulness, perceived ease of use, trust and price value) that have influence on users’ satisfaction in cloud-based payment systems in Australia. Qualtrics was used to gather the data of 411 respondents to an online questionnaire survey. After that, the PLS-SEM (Partial Least Square Structural Equation Modeling) analysis took place. The findings suggest that security, service quality, trust, perceived usefulness, and price value have impact on user satisfaction and this, in turn, affects CBPS adoption. Perceived ease of use has no influence on user satisfaction, and therefore, it has no impact on CBPS adoption. Besides, it was found that, overall, demographics have no impact on user satisfaction in CBPS.